1999
DOI: 10.1016/s0896-6273(00)81125-3
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Release of Ca2+ from IP3-Sensitive Stores Evoked by Synaptic Activation of mGluRs Paired with Backpropagating Action Potentials

Abstract: Increases in postsynaptic [Ca2+]i can result from Ca2+ entry through ligand-gated channels or voltage-gated Ca2+ channels, or through release from intracellular stores. Most attention has focused on entry through the N-methyl-D-aspartate (NMDA) receptor in causing [Ca2+]i increases since this pathway requires both presynaptic stimulation and postsynaptic depolarization, making it a central component in models of synaptic plasticity. Here, we report that repetitive synaptic activation of metabotropic glutamate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
387
6

Year Published

2002
2002
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 312 publications
(441 citation statements)
references
References 54 publications
48
387
6
Order By: Relevance
“…With extracellular stimulation of Schaffer collaterals (100 Hz; four pulses; 20 -50 A; 100 s duration), mGluR-mediated EPSCs were consistently evoked in CA1 pyramidal cells, as previously reported (Congar et al, 1997;Nakamura et al, 1999). A metabotropic response was, however, only observed with highresistance recording pipettes (n ϭ 10 and 28 for low-and highresistance pipettes, respectively) (Fig.…”
Section: A Single Ca3 Pyramidal Cell Does Not Induce Mglur-ltd In a Csupporting
confidence: 84%
“…With extracellular stimulation of Schaffer collaterals (100 Hz; four pulses; 20 -50 A; 100 s duration), mGluR-mediated EPSCs were consistently evoked in CA1 pyramidal cells, as previously reported (Congar et al, 1997;Nakamura et al, 1999). A metabotropic response was, however, only observed with highresistance recording pipettes (n ϭ 10 and 28 for low-and highresistance pipettes, respectively) (Fig.…”
Section: A Single Ca3 Pyramidal Cell Does Not Induce Mglur-ltd In a Csupporting
confidence: 84%
“…LTP has generally not been observed at synapses between parallel fibers and Purkinje cells. Purkinje cells require the synergistic action of mGluRs and a rise in IP 3 to release Ca 2ϩ from intracellular stores with voltage-sensitive Ca 2ϩ channels for the induction of LTD (39)(40)(41). In the absence of mGluR1 or of IP 3 receptors, LTD is not observed in Purkinje cells and motor coordination is abnormal (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…Back-propagating dendritic action potentials are likely to play an important role in triggering the increases in intracellular calcium necessary for DSI in these conditions (Morishita & Alger, 2001). Combining backpropagating action potentials with synaptic activation of mGluRs (Nakamura et al, 1999) was shown to induce increases in intracellular calcium in the micromolar range, thus well in the order of magnitude shown by Wang & Zucker (2000) to be required for DSI induction.…”
Section: Physiological Induction Protocols Of Hippocampal Dsimentioning
confidence: 95%